Characteristics of Driving Behavior on Dangerous Road, and Influences of Warning Information at Intersections - SUTO, Koji; FUJIWARA, Akimasa; ZHANG, Junyi (INFRASTRUCTURE PLANNING REVIEW, 2007)
In this paper, we attempted to analyze the spatial distribution of driving behavior by driving Advanced cruise-assist Highway Systems (AHS) Test-Car on the Smart 2miles Hiroshima, and the influences of Warning Information to drivers such as HMI (Human Machine Interface, e.g. voice and image from information onboard unit) at intersections where accidents eminently occur. As the results, we recognized that deceleration points more than 0.2G were occurring continuously but points more than 03G were limited spatially. And the subjects' characteristics of driving behavior were obvious by the G-G diagram method. Thus it was clear that the deceleration and the composite deceleration were differences among individual